Analisis Perspektif Semiotika Makna Kebaya Yang Ditampilkan Jeng Yah Dalam Serial Gadis Kretek - Amanda Safira Putri Hamid; Artyasto Jatisidi; Rocky Prasetyo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The series 'Gadis Kretek' carries a deep significance of Javanese society, firmly rooted in its principles, guidance, and cultural heritage. The series traces the history and development of the kretek industry against a historical backdrop. The character Dasiyah, or Jeng Yah, plays a crucial role in representing an inspiring woman. Her character demonstrates that women possess courage, perseverance, and the ability to overcome challenges. In this research, the focus will be on the colors of the kebaya worn by Dasiyah or Jeng Yah. This article employs a qualitative method with Roland Barthes' semiotic approach to analyze the perspectives and meanings conveyed by the kebaya worn by Jeng Yah in the Netflix series. The researcher has applied several methods, including a literature review, observation, and documentation. This is because the research object is a document, specifically the scenes in the Netflix film 'Gadis Kretek.